STUDY OF JAPANESE OCCUPATION IN SURAKARTA AS A FOUNDATION IN SITE MAPPING AND EDUCATION-RELATED HISTORICAL TOURISM - Sutiyah; Dadan Adi Kurniawan; Tri Yuniyanto (SOSIOEDUKASI, 2025)
This research aims to (1) Observe the policies of the Japanese Occupation Government in Surakarta in the political, socio-cultural and economic fields (2) Map the sites of the Japanese Occupation period in Surakarta for the development of historical tourism by prioritizing the value of education. This research uses a historical method, with the step of collecting data through the study of archives, documents and relevant previous research as well as related reference books; analyze sources to find the authenticity and credibility of sources; interpreting with political, sociological, and economic approaches to find the historical facts sought, and finally producing historiography about the Japanese occupation in Surakarta by mapping historical sites and tourism with educational content that can be scientifically accounted for. The results of the study show that (1), the Japanese Occupation Policy in Surakarta is top down, that is, it follows the policy of the Army government in Java by regulating local government. The government bureaucracy is territorial, from the highest to the lowest, held by indigenous people but with very strict supervision. In the social field, it is characterized by the loss of hierarchy based on race. In the field of culture and economy, Japan tried to Japaneseize but was not able to form its own culture, local culture was used to realize Japanese government programs, especially for the needs of winning wars; The economy is directed towards the war economy, so all economic activities are associated with the war victory effort. (2) There are not so many Japanese heritage sites in Surakarta, because of the Japanese colonial period which was only 3 1/2 years, but it left a deep impression. The impressions in question are related to Kenpei Tai, the recruitment of comfort women (Jugun Iyanfu), forced labor (romusya), poverty, the cruelty of the Japanese army and military training; Relics that can be mapped as educational tourism are such as: Kenpei Tai headquarters, MAPA Headquarters, street names, Japanese Caves, These relics can be packaged into tour packages that have educational value because there are values of strength, togetherness, unity, discipline and heroic spirit from the masses which are very valuable for Indonesia in the future.